PENGARUH KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP STRES KERJA DAN RETENSI KARYAWAN DI PT MULTI AUTO INTRAWAHANA PEKANBARU - Alpen Ripaldi; Marnis '; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted at PT. Multi Auto Intrawahana Pekanbaru. The purpose of this study was to determine the effect of job satisfaction and Organizational Citizenship Behavior (OCB) against work stress and its impact on the retention of employees at PT. Multi Auto Intrawahana Pekanbaru. Total population in this study were 53 employees and a sample is taken from the entire population of 53 employees. The determination of the sample using census method or technique of total sampling is a sampling technique that is done by taking the entire population. The results of the study of job satisfaction significant positive effect on employee retention, Organizational Citizenship Behavior (OCB) has no effect on employee retention, job stress significant negative effect on employee retention, job satisfaction significant negative effect on job stress of employees and Organizational Citizenship Behavior (OCB) negative effect significantly to the stress of employees of PT Multi Auto Intrawahana Pekanbaru. Advice can be given that the leaders should provide equitable opportunities for all employees in career development, to employees in order to always maintain good communication and continue to think positively with each other and the company should be able to pass training on cooperation and responsibility to cultivate an attitude and awareness of responsibility and cooperation on the employee.Keywords: Job satisfaction, Organizational Citizenship Behavior (OCB), work stress and Retention.